Energetics contribution during no-gi Brazilian jiu jitsu sparring and its association with regional body composition - Filho, Dalton Müller Pessôa [UNESP]; Sancassani, Andrei [UNESP]; da Cruz Siqueira, Leandro Oliveira [UNESP]; Massini, Danilo Alexandre [UNESP]; Santos, Luiz Gustavo Almeida [UNESP]; Neiva, Cassiano Merussi [UNESP]; DiMenna, Fred J. (Public Library of Science (PLoS), 2021)
We used measurements of metabolic perturbation obtained after sparring to estimate energetics contribution during no-gi Brazilian jiu-jitsu. Ten advanced grapplers performed two six-minute sparring bouts separated by 24 hours. Kinetics of recovery rate of oxygen uptake was modelled and post-combat-sparring blood-lactate concentration measured to estimate oxygen equivalents for phospholytic and glycolytic components of anaerobic energetics, respectively. Linear regression was used to estimate end-combat-sparring rate of oxygen uptake. Regional and whole-body composition were assessed using dual X-ray absorptiometry with associations between these measurements and energy turnover explored using Pearson’s correlation coefficient (significance, P < 0.05). Estimated oxygen equivalents for phospholytic and glycolytic contributions to anaerobic metabolism were 16.9 ± 8.4 (~28%) and 44.6 ± 13.5 (~72%) mLkg-1, respectively. Estimated end-exercise rate of oxygen uptake was 44.2 ± 7.0 mLkg-1min-1. Trunk lean mass was positively correlated with both total anaerobic and glycolytic-specific energetics (total, R = 0.645, p = 0.044; glycolytic, R = 0.692, p = 0.027) and negatively correlated with end-exercise rate of oxygen uptake (R = -0.650, p = 0.042). There were no correlations for any measurement of body composition and phospholytic-specific energetics. Six minutes of no-gi Brazilian jiu-jitsu sparring involves high relative contribution from the glycolytic component to total anaerobic energy provision and the link between this energetics profile and trunk lean mass is consistent with the predominance of ground-based combat that is unique for this combat sport. Training programs for Brazilian jiu-jitsu practitioners should be designed with consideration given to these specific energetics characteristics.